A Perception of z generation on halal brand personality in Indonesia - Kumala, Nafa Indah; Ali, Dini Salmiyah (Universitas Airlangga, 2023)
The growth of various halal industry sectors around the world is increasing year by year. However, halal fashion as the third rank still has a fairly slow growth compared to the Islamic finance sector and halal food as the first and second-ranked halal industry sectors. Indonesia, with the largest number of Muslims in the world, will certainly feel the impact and benefit from this growth. This research aims to the Z generation's perception of halal brand personality in Indonesia using the concept of halal brand personality from Ahmad (2015) which is adopted from Aaker's theory (1997) and contains 5 dimensions: purity, excitement, safety, sophistication, and righteousness. This research uses a descriptive qualitative method and the data collection using focused group discussions with 7 SOKA's Instagram followers and product users. The result showed that purity is perceived as pure and friendly, excitement as up-to-date, safety as feeling safe, sophistication as high-class, and righteousness as spiritual.